2005
DOI: 10.1097/01.mlr.0000167181.36730.cc
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perception and Impact of Severe Acute Respiratory Syndrome (SARS) on Work and Personal Lives of Healthcare Workers in Singapore

Abstract: During epidemics, healthcare institutions have a duty to protect HCWs and help them cope with their personal fears and the very stressful work situation. Singapore's experience shows that simple protective measures based on sound epidemiological principles, when implemented in a timely manner, go a long way to reassure HCWs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
563
12
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 452 publications
(628 citation statements)
references
References 16 publications
41
563
12
12
Order By: Relevance
“…Our results are also consistent with other studies that found that most HCWs have greater stress and workload, work overtime and do work normally done by others during an infectious disease outbreak 1,4) . A higher percentage of TH HCWs felt that there would be more conflict amongst colleagues at work and the need to work overtime.…”
Section: Perceived Impact On Personal Life and Worksupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are also consistent with other studies that found that most HCWs have greater stress and workload, work overtime and do work normally done by others during an infectious disease outbreak 1,4) . A higher percentage of TH HCWs felt that there would be more conflict amongst colleagues at work and the need to work overtime.…”
Section: Perceived Impact On Personal Life and Worksupporting
confidence: 93%
“…The questionnaire was developed from an earlier survey used in a study of SARS and HCWs 1) . Participation was voluntary and ethics approval was provided by each hospital's Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the earlier epidemic waves, HCWs experienced extreme stress, lifestyle effects, and, to a long extent, psychological sequelae (6) , which were apparent in the most recent outbreaks of MERS-CoV, Ebola, and SARS (7)(8)(9) . Furthermore, social consequences could result, such as social avoidance, anxiety of family members, and loss of support from the employer.…”
mentioning
confidence: 99%